Research on the impact of hospital organizational behavior on physicians'patient-centered care - Pengwei Zhang; Haotong Zhang; Angyang Wang (Archives of Public Health)
Abstract Objectives This study seeks to examine the impact of hospital organizational behavior on Physicians' Patient-centered care and aims to offer innovative insights and strategies for enhancing the quality of healthcare services. Methods A conceptual model was developed based on organizational behavior theory. Data were collected via questionnaires from 10 large public hospitals in China, encompassing eight independent variables, including hospital organizational culture, change behavior, and motivational behavior, as well as moderating variables like physician title and control variables such as personality traits. SPSS software was used for descriptive statistics, correlation analysis, covariance testing, and multiple linear regression analysis. Results (1) The study of the 10 large public hospitals revealed a coexistence of four types of organizational cultures. Support-oriented and innovation-oriented cultures were dominant, followed by rule-oriented cultures, while goal-oriented cultures scored relatively low. Additionally, these hospitals showed effective organizational change behaviors in technology and resource optimization, as well as inter-professional teamwork. Incentives related to employee welfare systems and development programs also demonstrated high implementation effectiveness. (2) Supportive and innovation-oriented hospital cultures positively influence Physicians' Patient-centered care, while goal-oriented cultures negatively impact Physicians' Patient-centered care. (3) In public hospitals, organizational change behaviors such as technology and resource optimization, along with inter-professional teamwork, positively influence Physicians' Patient-centered care. Additionally, organizational incentives like employee welfare systems and training programs enhance Physicians' Patient-centered care. (4) The moderating variable of physician title negatively affects the relationship between the employee welfare system and Physicians' Patient-centered care, as well as the relationship between the staff development program and Physicians' Patient-centered care. Conclusions Hospital organizational behavior significantly impacts Physicians’ Patient-centered care. Supportive and innovative cultures, effective change behaviors, and incentives enhance Physicians’ Patient-centered care. Addressing limited resources and high demand is essential for optimizing healthcare service quality.